Karta Kamchatskago zaliva sostavlena po glazomi︠e︡rnoĭ sʺemki︠e︡ i promi︠e︡ru Shkhipera shkhuny "Storozhʺ" F. Gekʺ vʺ 1900 g. / Chertilʺ khimich. tushʹi︠u︡ M. Posisi︠e︡evʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1902)
Relief shown by hachures. Depth shown by soundings.; Includes inset map and five illustrations of the coastline of Kamchatka.; Inset map: "Planʺ ustʹi︠a︡ ri︠e︡ki Kamchatki po opisi Kreĭsera "Afrika" 1882 g." = Plan of the mouth of the Kamchatka river according to the survey of the cruiser "Africa" in 1882.; Top margin title translation: Eastern Sea, southeastern coast of Kamchatka; Greenwich meridian.; "No. 580" -- bottom right margin Color; 1:900,000